2018
DOI: 10.29241/jmk.v4i1.102
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Keberhasilan Pengobatan Multi Drug Therapy Pada Penderita Kusta Tipe Multibaciler

Abstract: ABSTRAK Pengobatan MDT pada penderita kusta tipe Multibaciler (MB) adalah kegiatan menelan minum obat MDT secara intensif selama 12 bulan bagi penderita kusta tipe MB di Provinsi Sulawesi Selatan. Penyakit kusta tipe MB tidak dapat menyebabkan kematian, akan tetapi bila tidak menjalani pengobatan MDT menyebabkan kecacatan, masalah psikososial, stigma, dan penurunan produktivitas. Penelitian ini bertujuan untuk menganalisis faktor yang mempengaruhi keberhasilam pengobatan MDT pada penderita kusta tipe MB di Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…According to Wawan Dewi 2011 there are 2 factors that influence knowledge, namely internal factors including education, employment, age and external factors in the form of environmental and socio-cultural factors (Wawan & Dewi, 2011). Rustam's 2018 research shows that there is a relationship between knowledge and medication adherence (Rustam, 2018). Based on Fatmala's research, it was found that the risk of patients not adhering to taking medication in patients with low knowledge was 7.36 times greater than patients with high knowledge (Fatmala, 2016).…”
Section: Knowledge Of Medicinementioning
confidence: 99%
See 3 more Smart Citations
“…According to Wawan Dewi 2011 there are 2 factors that influence knowledge, namely internal factors including education, employment, age and external factors in the form of environmental and socio-cultural factors (Wawan & Dewi, 2011). Rustam's 2018 research shows that there is a relationship between knowledge and medication adherence (Rustam, 2018). Based on Fatmala's research, it was found that the risk of patients not adhering to taking medication in patients with low knowledge was 7.36 times greater than patients with high knowledge (Fatmala, 2016).…”
Section: Knowledge Of Medicinementioning
confidence: 99%
“…Based on Rustam's research, there is an influence between the role of health workers and medication adherence. Because officers are able to educate well about information on length of treatment, rules for taking medication, and information about other leprosy using language that is easy to understand (Rustam, 2018).…”
Section: Success Factors In the Treatment Of Type Mb Leprosy Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pada tahun 1970an karena keterbatasan transportasi serta keterjangkauan lokasi Puskesmas sehingga akses masyarakat untuk pengobatan kusta sulit sedangkan masa sekarang ini sudah ada Puskesmas yang lebih dekat yang berada di Pulau Mantang Besar. Ketersedian obat dan peran petugas kesehatan yang baik serta sarana pelayanan kesehatan mempunyai pengaruh terhadap probabilitas penderita untuk patuh meminum obat (18) . Namun berbeda di beberapa temuan penelitian lain tidak terdapat hubungan antara akses ke pelayanan kesehatan terhadap keberhasilan pengobatan penderita kusta (19) (20) .…”
Section: Bahasanunclassified